Методика комплексной оценки динамичности военных гусеничных и колесных машин на этапе структурно-параметрического синтеза их трансмиссий - Волонцевич, Дмитрий Олегович; Веретенников, Евгений Александрович (НТУ "ХПИ", 2011)
In article the new criterion for an estimation of dynamism of military caterpillar and wheel machines in view of the law of roads types, on which the machine is maintained, distribution. The technique of definition of the offered criterion is resulted. It allows to compare by criterion of machine dynamism within the limits of a corresponding category and to use it as one of criteria of optimization at structurally-parametrical synthesis of any types of transmissions
Keywords: машины военного назначения; дорожные условия; разгон